Perancangan Arsitektur Sistem Antrian Online Terintegrasi BPJS di RSU Queen Latifa Berbasis Docker - Dimas Rizki Setyaji; Danur Wijayanto (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2025)
This research focuses on designing an online queuing system architecture that is integrated with BPJS at Queen Latifa Hospital using Docker-based containerization technology. This system is designed to improve service efficiency by utilizing Proxmox as the main server infrastructure to support flexibility and scalability. With a Docker-based approach, each system component is packaged in an isolated container to ensure stability, efficiency, and cross-platform compatibility. The design process includes server architecture modeling, BPJS service integration, and queue data management in a systematic and structured manner. The design also supports automation in development and deployment through GitHub Actions-based CI/CD, which aims to minimize errors in system updates. In addition, aspects of data security, service availability, and efficient use of resources are the main factors in technology selection and system configuration. The system is designed to optimize patient queue management, reduce waiting time, and improve the quality of hospital services. With the containerization approach, the system can be easily adapted to user needs and future technological developments. This design is the basis for developing a system that is more scalable, flexible, and can be applied to various healthcare environments with maximum efficiency.